Negative electrode active material and negative electrode
Patent Information
- Application Number
- JP2022002143
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-01-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-01-11
AI Technical Summary
【0044】 以上のように、本発明の負極活物質であれば、十分な電池サイクル特性を実現しつつ、スラリー化時の安定性を高めることができる。
Smart Images

Figure 0007601807000006 
Figure 0007601807000007 
Figure 0007601807000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode active material and a negative electrode. [Background technology]
[0002] In recent years, small electronic devices such as mobile terminals have become widespread, and there is a strong demand for further miniaturization, weight reduction, and longer life. In response to such market demands, development of secondary batteries that are small, lightweight, and capable of obtaining high energy density has been promoted. The application of these secondary batteries is being considered not only for small electronic devices, but also for large electronic devices such as automobiles and power storage systems such as homes.
[0003] Among these, lithium-ion secondary batteries are attracting great attention because they can be easily made small and have a high capacity, and because they can provide a higher energy density than lead batteries or nickel-cadmium batteries.
[0004] The lithium ion secondary battery includes a positive electrode, a negative electrode, a separator, and an electrolyte solution, and the negative electrode contains a negative electrode active material involved in charge and discharge reactions.
[0005] While carbon-based active materials are widely used as negative electrode active materials, recent market demands have called for further improvements in battery capacity. To improve battery capacity, the use of silicon as a negative electrode active material is being considered. This is because the theoretical capacity of silicon (4199mAh / g) is more than 10 times greater than the theoretical capacity of graphite (372mAh / g), and a significant improvement in battery capacity can be expected. In the development of silicon materials as negative electrode active materials, not only silicon itself but also compounds such as alloys and oxides are being considered. In addition, the active material shape is being considered, ranging from the standard coating type for carbon-based active materials to an integrated type that is directly deposited on the current collector.
[0006] However, when silicon is used as the main raw material for the negative electrode active material, the negative electrode active material expands and contracts during charging and discharging, making it prone to cracking, mainly near the surface layer of the negative electrode active material. In addition, ionic substances are generated inside the active material, making the negative electrode active material prone to cracking. When the surface layer of the negative electrode active material cracks, a new surface is created, increasing the reaction area of the active material. At this time, a decomposition reaction of the electrolyte occurs on the new surface, and a coating, which is a decomposition product of the electrolyte, is formed on the new surface, consuming the electrolyte. This makes the cycle characteristics more likely to deteriorate.
[0007] To date, various studies have been conducted on negative electrode materials and electrode configurations for lithium-ion secondary batteries that are primarily made of silicon materials in order to improve the initial efficiency and cycle characteristics of the battery.
[0008] Specifically, in order to obtain good cycle characteristics and high safety, silicon and amorphous silicon dioxide are simultaneously deposited using a gas phase method (see, for example, Patent Document 1). Also, in order to obtain high battery capacity and safety, a carbon material (electron conductive material) is provided on the surface layer of silicon oxide particles (see, for example, Patent Document 2). Furthermore, in order to improve cycle characteristics and obtain high input / output characteristics, an active material containing silicon and oxygen is prepared, and an active material layer with a high oxygen ratio is formed near the current collector (see, for example, Patent Document 3). Also, in order to improve cycle characteristics, oxygen is contained in the silicon active material, and the active material is formed so that the average oxygen content is 40 at% or less and the oxygen content is high in the area close to the current collector (see, for example, Patent Document 4).
[0009] In addition, in order to improve the initial charge / discharge efficiency, the Si phase, SiO2, and M y Nanocomposites containing metal oxides are used (see, for example, Patent Document 5). In addition, in order to improve cycle characteristics, SiO x(0.8 ≤ x ≤ 1.5, particle size range = 1 μm to 50 μm) is mixed with a carbon material and fired at a high temperature (see, for example, Patent Document 6). Further, in order to improve cycle characteristics, the molar ratio of oxygen to silicon in the negative electrode active material is set to 0.1 to 1.2, and the active material is controlled within a range where the difference between the maximum value and the minimum value of the molar ratio near the interface between the active material and the current collector is 0.4 or less (see, for example, Patent Document 7). Further, in order to improve the battery load characteristics, a metal oxide containing lithium is used (see, for example, Patent Document 8). Further, in order to improve cycle characteristics, a hydrophobic layer such as a silane compound is formed on the surface layer of the silicon material (see, for example, Patent Document 9). Further, in order to improve cycle characteristics, silicon oxide is used, and conductivity is imparted by forming a graphite film on its surface layer (see, for example, Patent Document 10). In Patent Document 10, regarding the shift value obtained from the RAMAN spectrum of the graphite film, broad peaks appear at 1330 cm -1 and 1580 cm -1 and the intensity ratio I 1330 / I 1580 is 1.5 < I 1330 / I 1580 < 3. Further, in order to improve high battery capacity and cycle characteristics, particles having a silicon microcrystalline phase dispersed in silicon dioxide are used (see, for example, Patent Document 11). Further, in order to improve overcharge and overdischarge characteristics, a silicon oxide in which the atomic ratio of silicon to oxygen is controlled to 1:y (0 < y < 2) is used (see, for example, Patent Document 12).
[0010] The lithium-ion secondary battery using silicon oxide was shipped by Hitachi Maxell in June 2010 for a rectangular secondary battery for smartphones that employs a nanosilicon composite (see, for example, Non-Patent Document 1). The silicon oxide proposed by Hohl is Si 0+ ~Si 4+It is a composite material with various oxidation states (see Non-Patent Document 2). Kapaklis has also proposed a disproportionated structure in which silicon oxide is separated into Si and SiO2 by applying a thermal load to the silicon oxide (see Non-Patent Document 3). Miyachi et al. have focused on Si and SiO2, which contribute to charging and discharging, among silicon oxides with disproportionated structures (see Non-Patent Document 4), and Yamada et al. have proposed the following reaction formula between silicon oxide and Li (see Non-Patent Document 5).
[0011] 2SiO(Si+SiO2) + 6.85Li + + 6.85e - → 1.4Li 3.75 Si + 0.4Li4SiO4 + 0.2SiO2
[0012] The above reaction formula shows that Si and SiO2 that make up silicon oxide react with Li, and are separated into Li silicide, Li silicate, and some unreacted SiO2.
[0013] The Li silicate formed here is irreversible, and once formed, it is considered to be a stable substance that does not release Li. The capacity per mass calculated from this reaction formula is close to the experimental value, and is recognized as the reaction mechanism of silicon oxide. Kim et al. have defined the irreversible component associated with the charge and discharge of silicon oxide, Li silicate, as Li4SiO4, and 7 Li-MAS-NMR and 29 The identification was carried out using Si-MAS-NMR (see Non-Patent Document 6).
[0014] This irreversible capacity is the weakest point of silicon oxide, and there is a need to improve it. Kim et al. have used a Li pre-doping method to form Li silicate in advance, which significantly improves the initial efficiency of the battery and creates a negative electrode that can withstand practical use (see Non-Patent Document 7).
[0015] Also, instead of doping the electrode with Li, a method of treating the powder has been proposed, which has achieved an improvement in irreversible capacity (see Patent Document 13). [Prior art documents] [Patent documents]
[0016] [Patent Document 1] JP 2001-185127 A [Patent Document 2] JP 2002-042806 A [Patent Document 3] JP 2006-164954 A [Patent Document 4] JP 2006-114454 A [Patent Document 5] JP 2009-070825 A [Patent Document 6] JP 2008-282819 A [Patent Document 7] JP 2008-251369 A [Patent Document 8] JP 2008-177346 A [Patent Document 9] JP 2007-234255 A [Patent Document 10] JP 2009-212074 A [Patent Document 11] JP 2009-205950 A [Patent Document 12] Japanese Patent Application Publication No. 06-325765 [Patent Document 13] JP 2015-156355 A [Non-patent literature]
[0017] [Non-Patent Document 1] Battery Association of Japan's journal "Denchi", May 1, 2010 issue, page 10 [Non-Patent Document 2] A. Hohl, T. Wieder, P. A. van Aken, T. E. Weirich, G. Denninger, M. Vidal, S. Oswald, C. Deneke, J. Mayer, and H. Fuess: J. Non-Cryst. Solids, 320, (2003), 255. [Non-Patent Document 3] V. Kapaklis, J. Non-Crystalline Solids, 354 (2008) 612 [Non-Patent Document 4] Mariko Miyachi, Hironori Yamamoto, and Hidemasa Kawai, J. Electrochem. Soc. 2007 volume 154, issue 4, A376-A380 [Non-Patent Document 5] M. Yamada, M. Inaba, A. Ueda, K. Matsumoto, T. Iwasaki, T. Ohzuku, J.Electrochem. Soc., 159, A1630 (2012) [Non-Patent Document 6] Taeahn Kim, Sangjin Park, and Seung M. Oh, J. Electrochem. Soc. volume 154, (2007), A1112-A1117. [Non-Patent Document 7] Hye Jin Kim, Sunghun Choi, Seung Jong Lee, Myung Won Seo, Jae Goo Lee, Erhan Deniz, Yong Ju Lee, Eun Kyung Kim, and Jang Wook Choi,. Nano Lett. 2016, 16, 282-288. [Summary of the Invention] [Problems to be Solved by the Invention]
[0018] As mentioned above, in recent years, small electronic devices such as mobile terminals have been improved in performance and functionality, and lithium-ion secondary batteries, which are the main power sources for these devices, are required to have increased battery capacity. As one method to solve this problem, the development of lithium-ion secondary batteries consisting of a negative electrode mainly made of silicon material is desired. In addition, lithium-ion secondary batteries using silicon material are desired to have initial charge / discharge characteristics and cycle characteristics similar to those of lithium-ion secondary batteries using carbon-based active materials. Therefore, the cycle characteristics and initial charge / discharge characteristics have been improved by using (Li-doped) silicon oxide modified by insertion of Li and partial desorption of the inserted Li as the negative electrode active material. However, when the negative electrode material into which Li is inserted is used in the slurry in the electrode formation process, various problems have occurred, such as a decrease in the viscosity of the binder (thickener) due to partial elution of the Li component in the slurry.
[0019] The present invention has been made in consideration of the above problems, and has an object to provide a negative electrode active material that can improve stability during slurrying while realizing sufficient battery cycle characteristics, and a negative electrode including such a negative electrode active material. [Means for solving the problem]
[0020] In order to solve the above problems, the present invention provides a negative electrode active material including negative electrode active material particles, The negative electrode active material particles contain silicon oxide particles coated with a carbon layer, At least a portion of the silicon oxide particles contains at least one selected from the group consisting of Li2SiO3, Li4SiO4, and Li6Si2O7, The present invention provides an anode active material, characterized in that at least a part of the outermost layer of the anode active material particles is covered with a layer of a plasticizer.
[0021] The negative electrode active material of the present invention contains negative electrode active material particles that contain silicon oxide particles, and therefore can improve the battery capacity.
[0022] In addition, in the negative electrode active material of the present invention, at least a part of the silicon oxide particles contains at least one selected from the group consisting of Li2SiO3, Li4SiO4, and Li6Si2O7, and at least a part of the outermost layer of the negative electrode active material particles is coated with a plasticizer layer, so that excellent Li diffusibility in the bulk can be obtained while significantly improving water resistance. By improving the Li diffusibility, the battery cycle characteristics can be improved.
[0023] As a result, the negative electrode active material of the present invention can achieve sufficient battery cycle characteristics while improving stability when made into a slurry.
[0024] The thickness of the plasticizer layer is preferably 0.1 nm or more and 10 nm or less.
[0025] If the thickness of the plasticizer layer is within this range, the thickness can be easily controlled and sufficient Li permeability can be exhibited.
[0026] It is preferable that the carbon layer partially contains nitrogen atoms.
[0027] Such carbon layers can exhibit good stability and good Li permeability.
[0028] In this case, the carbon layer is formed using a hydrocarbon material derived from petroleum asphalt as a starting material, and may contain the nitrogen atoms as a part thereof.
[0029] The carbon layer may be formed starting from a hydrocarbon material derived from petroleum asphalt.
[0030] The plasticizer desirably includes at least one selected from the group consisting of phthalate ester plasticizers, adipate ester plasticizers, phosphate ester plasticizers, and sulfonamide plasticizers.
[0031] If the outermost layer is coated with a layer containing such a plasticizer, excellent water resistance can be more reliably exhibited.
[0032] It is more desirable that the plasticizer contains at least one selected from the group consisting of dioctyl phthalate, dibutoxyethyl phthalate, diisononyl phthalate, diisodecyl phthalate, diundecyl phthalate, bis(2-ethylhexyl) adipate, diisononyl adipate, diisodecyl adipate, bis(2-butoxyethyl) adipate, triphenyl phosphate, phthalic acid-based polyesters, adipic acid-based polyesters, epoxidized vegetable oils, p-toluenesulfonamide, N-ethyl-o-toluenesulfonamide, N-ethyl-p-toluenesulfonamide, o-toluenesulfonamide, p-toluenesulfonamide, Nn-butylbenzenesulfonamide, and N-cyclohexyl-p-toluenesulfonamide.
[0033] If the outermost layer is coated with a layer containing such a plasticizer, excellent water resistance can be more reliably exhibited.
[0034] The plasticizer layer preferably further contains a solid electrolyte.
[0035] When the plasticizer layer further contains a solid electrolyte, the negative electrode active material can exhibit better Li diffusibility.
[0036] In this case, the solid electrolyte may contain lithium phosphate and / or aluminum oxide.
[0037] For example, the solid electrolyte may include lithium phosphate and / or aluminum oxide.
[0038] The negative electrode active material particles have a peak attributable to a Si(111) crystal plane obtained by X-ray diffraction using Cu-Kα radiation before charging and discharging the negative electrode active material particles, the crystallite size corresponding to the crystal plane is 5.0 nm or less, and the ratio A / B of the intensity A of the peak attributable to the Si(111) crystal plane to the intensity B of the peak attributable to the Li2SiO3(111) crystal plane satisfies the following formula (1): 0.4≦A / B≦1.0 (1) It is preferable that the above formula is satisfied.
[0039] A negative electrode active material containing such negative electrode active material particles can achieve high battery capacity while reducing irreversible capacity.
[0040] The negative electrode active material particles preferably have a median diameter of 4.5 μm or more and 15 μm or less.
[0041] If the median diameter of the negative electrode active material particles is within this range, promotion of the reaction with the electrolyte can be prevented, and loss of electronic contacts due to expansion of the active material accompanying charge and discharge can be prevented.
[0042] The present invention also provides a negative electrode comprising the negative electrode active material of the present invention.
[0043] The negative electrode of the present invention includes the negative electrode active material of the present invention, and therefore can achieve sufficient battery cycle characteristics. Effect of the Invention
[0044] As described above, the negative electrode active material of the present invention can achieve sufficient battery cycle characteristics while improving stability when made into a slurry.
[0045] Furthermore, the negative electrode of the present invention can achieve sufficient battery cycle characteristics. [Brief description of the drawings]
[0046] [Figure 1]FIG. 1 is a schematic cross-sectional view showing an example of the configuration of a negative electrode of the present invention. [Diagram 2] FIG. 1 is an exploded view showing a configuration example (laminate film type) of a lithium ion secondary battery including a negative electrode of the present invention. [Diagram 3] 1 is an X-ray photoelectron spectroscopy spectrum of the surface of the negative electrode active material of Example 1. [Figure 4] 1 is a TOF-SIMS spectrum of the surface of the negative electrode active material of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0047] As mentioned above, as one method for increasing the battery capacity of a lithium-ion secondary battery, the use of a negative electrode mainly made of silicon oxide as the negative electrode of the lithium-ion secondary battery has been considered. It is desired that the lithium-ion secondary battery using this silicon oxide exhibits initial charge-discharge characteristics similar to those of a lithium-ion secondary battery using a carbon-based active material. In addition, in Li-doped SiO, which can improve the initial charge-discharge characteristics, it is desired that the cycle characteristics are similar to those of a carbon-based active material. However, it has not yet been proposed a negative electrode active material that can satisfy the pot life of the slurry when it is made into a slurry.
[0048] Therefore, the present inventors have conducted extensive research to obtain a negative electrode active material that is easy to handle and has high cycle characteristics when used as a negative electrode active material for a secondary battery. As a result, the inventors have found that the Li silicate phase obtained by doping silicon oxide with Li can be kept in at least one state selected from the group consisting of Li2SiO3, Li4SiO4, and Li6Si2O7, which are easily dissolved in water but have high Li diffusivity, by suppressing the generation of Li2Si2O5, and by covering the outermost layer of the negative electrode active material with a layer of plasticizer, excellent Li diffusivity in the bulk can be obtained while significantly improving water resistance, and have completed the present invention.
[0049] That is, the present invention provides a negative electrode active material including negative electrode active material particles, The negative electrode active material particles contain silicon oxide particles coated with a carbon layer, At least a portion of the silicon oxide particles contains at least one selected from the group consisting of Li2SiO3, Li4SiO4, and Li6Si2O7, The negative electrode active material is characterized in that at least a part of the outermost layer of the negative electrode active material particles is covered with a layer of a plasticizer.
[0050] The present invention also provides a negative electrode comprising the negative electrode active material of the present invention.
[0051] The present invention will be described in detail below, but the present invention is not limited thereto.
[0052] [Negative electrode active material] The negative electrode active material of the present invention (hereinafter also referred to as silicon-based negative electrode active material) contains negative electrode active material particles (hereinafter also referred to as silicon-based negative electrode active material particles) that contain silicon oxide particles, and therefore can improve battery capacity.
[0053] In addition, by forming Li silicate on at least a part of the silicon oxide particles, it becomes possible to stabilize the slurry before application, and by using a stable slurry, a good electrode can be obtained and the battery characteristics can be improved. However, it was found that such a slurry does not have sufficient long-term storage stability, and the formed Li silicate slowly dissolves in the slurry over time.
[0054] When Li silicate is formed, for example, by applying a heat load, the crystalline phase of Li silicate can be enlarged, which reduces the amount of Li dissolved in the slurry, but at the same time, the crystallinity of Si increases. The formation of such highly crystalline Si is a factor that significantly reduces the battery characteristics.
[0055] Furthermore, when the Li silicate phase becomes enlarged, the diffusibility of Li is significantly reduced, resulting in deterioration of the battery characteristics.
[0056] Therefore, by making the Li silicate crystal phase as small as possible and suppressing the crystallization of Si and the enlargement of the Li silicate phase, a Li silicate phase that dissolves slowly in water is generated.
[0057] As a result, sufficient battery characteristics were obtained; however, in the electrode formation process, particularly in the preparation of the slurry, if the slurry was left for a long time, the binder would deteriorate and the battery characteristics would deteriorate, so it was necessary to apply the slurry as soon as possible after its preparation.
[0058] Therefore, the inventors have developed a material that can obtain excellent Li diffusivity within the bulk while significantly improving water resistance by keeping the Li silicate phase in at least one state selected from the group consisting of Li2SiO3, Li4SiO4, and Li6Si2O7 and coating the outermost layer of the negative electrode active material with a layer of plasticizer.
[0059] In the negative electrode active material of the present invention, at least a part of the silicon oxide particles contains at least one selected from the group consisting of Li2SiO3, Li4SiO4, and Li6Si2O7, and at least a part of the outermost layer of the negative electrode active material particles is coated with a plasticizer layer, thereby significantly improving water resistance and obtaining excellent Li diffusibility in the bulk. By improving the Li diffusibility, the battery cycle characteristics can be improved.
[0060] Therefore, the negative electrode active material of the present invention can achieve sufficient battery cycle characteristics while improving stability when made into a slurry.
[0061] The negative electrode active material of the present invention will be described in more detail below.
[0062] The negative electrode active material of the present invention can be used, for example, as a negative electrode active material for non-aqueous electrolyte secondary batteries, particularly for lithium ion secondary batteries.
[0063] The negative electrode active material of the present invention contains silicon oxide particles. The silicon oxide particles can be said to be a silicon oxide material containing a silicon compound containing oxygen. The ratio of silicon to oxygen constituting this silicon oxide is SiO x It is preferable that the range of x is 0.8≦x≦1.2. If x is 0.8 or more, the oxygen ratio is higher than that of silicon alone, and therefore the cycle characteristics are good. If x is 1.2 or less, the resistance of the silicon oxide does not become too high, which is preferable. Among these, SiO x In the composition, it is preferable that x is close to 1, because high cycle characteristics can be obtained. Note that the composition of the silicon compound in the present invention does not necessarily mean 100% purity, and may contain trace amounts of impurity elements.
[0064] In the negative electrode active material of the present invention, the silicon oxide particles contain at least one Li compound, specifically, at least one selected from the group consisting of Li2SiO3, Li4SiO4, and Li6Si2O7, in at least a part thereof. More specifically, it is preferable that the silicon oxide particles contain Li2SiO3. In such a case, the SiO2 component part in the silicon oxide, which becomes unstable when lithium is inserted and removed during charging and discharging of the battery, is modified to another lithium silicate in advance, so that the irreversible capacity generated during charging can be reduced. In addition, the irreversible capacity associated with charging and discharging can be reduced by enlarging the Li silicate within a range in which the crystal growth of Si is suppressed. Therefore, it is desirable that Li2SiO3 among the Li silicates generated in the bulk has crystallinity.
[0065] However, if it becomes too large, it will no longer contribute to charging and discharging, so there is an optimal range.
[0066] When made into a slurry, Li4SiO4 and Li6Si2O7 are more unstable than Li2SiO3 due to their high solubility in water, but they can be used effectively by improving their water resistance using the plasticizer described below.
[0067] In this case, Li4SiO4 has the best Li diffusibility, and it is desirable to use it in combination with Li2SiO3, which has high structural stability.
[0068] In addition, Li silicates such as Li2SiO3, Li4SiO4, and Li6Si2O7 contained inside the bulk of silicon oxide particles can be quantified by NMR (Nuclear Magnetic Resonance). NMR measurement can be performed, for example, under the following conditions. 29 Si-MAS-NMR (Magic Angle Spinning Nuclear Magnetic Resonance) Equipment: Bruker 700 NMR spectrometer; Probe: 4mm HR-MAS rotor 50μL, Sample rotation speed: 10kHz, ·Measurement environment temperature: 25℃.
[0069] The degree of Li silicate enlargement and the degree of Si crystallization can be confirmed by XRD (X-ray Diffraction). The X-ray diffractometer used can be a Bruker D8 ADVANCE. For example, the X-ray source is a Cu Kα ray, and a Ni filter is used, with an output of 40 kV / 40 mA, a slit width of 0.3°, a step width of 0.008°, and a counting time of 0.15 seconds per step, for measurements from 10 to 40°.
[0070] The negative electrode active material particles contained in the negative electrode active material of the present invention have a peak due to a Si(111) crystal plane obtained by X-ray diffraction using Cu-Kα radiation before charging and discharging the negative electrode active material particles, the crystallite size corresponding to the crystal plane is 5.0 nm or less, and the ratio A / B of the intensity A of the peak due to the Si(111) crystal plane to the intensity B of the peak due to the Li2SiO3(111) crystal plane satisfies the following formula (1): 0.4≦A / B≦1.0 (1) It is preferable that the above formula is satisfied.
[0071] A negative electrode active material containing such negative electrode active material particles can achieve high battery capacity while reducing irreversible capacity.
[0072] In the negative electrode active material of the present invention, the silicon oxide particles are coated with a carbon layer, which can improve the battery capacity and safety.
[0073] The carbon that covers the silicon oxide particles is generally derived from hydrocarbon gas and formed using the CVD method, but by mixing the silicon oxide particles with asphalt components (hydrocarbon materials derived from petroleum asphalt) and heat treating them, nitrogen atoms (N) are contained. The carbon layer derived from asphalt has a molecular structure with a large number of carbon atoms. The presence of such a carbon layer makes it possible to improve water resistance when slurried. In addition, since the molecular structure with a large number of carbon atoms exhibits characteristics similar to pitch coat, which suppresses excessive decomposition of the electrolyte, it is difficult for decomposition products of the electrolyte to be excessively generated on the surface, and as a result, a coating with excellent Li permeability can be formed. As a result, a carbon layer that is more stable and has excellent Li permeability can be obtained.
[0074] In the negative electrode active material of the present invention, at least a part of the outermost layer of the negative electrode active material particles is covered with a plasticizer layer.
[0075] The thickness of the plasticizer layer is preferably 0.1 nm or more and 10 nm or less.
[0076] If the thickness of the plasticizer layer is within this range, the thickness can be easily controlled and sufficient Li permeability can be exhibited.
[0077] The plasticizer desirably contains at least one selected from the group consisting of phthalate ester plasticizers, adipate ester plasticizers, phosphate ester plasticizers, and sulfonamide plasticizers.
[0078] If the outermost layer is coated with a layer containing such a plasticizer, excellent water resistance can be more reliably exhibited.
[0079] Other plasticizers include Sebacic acid The plasticizer may contain an ester-based plasticizer, a glycol ester-based plasticizer, or an epoxy fatty acid ester-based plasticizer.
[0080] It is more desirable that the plasticizer essentially contains at least one selected from the group consisting of dioctyl phthalate, dibutoxyethyl phthalate, diisononyl phthalate, diisodecyl phthalate, diundecyl phthalate, bis(2-ethylhexyl) adipate, diisononyl adipate, diisodecyl adipate, bis(2-butoxyethyl) adipate, triphenyl phosphate, phthalic acid-based polyesters, adipic acid-based polyesters, epoxidized vegetable oils, p-toluenesulfonamide, N-ethyl-o-toluenesulfonamide, N-ethyl-p-toluenesulfonamide, o-toluenesulfonamide, p-toluenesulfonamide, Nn-butylbenzenesulfonamide, and N-cyclohexyl-p-toluenesulfonamide.
[0081] If the outermost layer is coated with a layer containing such a plasticizer, excellent water resistance can be more reliably exhibited.
[0082] The outermost plasticizer layer can be identified by X-ray Photoelectron Spectroscopy (XPS) and / or Time of Flight Secondary Ion Mass Spectrometry (TOF-SIMS).
[0083] XPS can be performed using, for example, PHI Quantera II manufactured by ULVAC-PHI, Inc. The X-ray beam diameter is 100 μm, and a neutralization gun can be used.
[0084] TOF-SIMS can be performed using, for example, TOF-SIMS5 manufactured by ION-TOF, Inc. Examples of conditions are shown below. Mass range (m / z) 0~1500 Raster size 300μm□ Number of scans: 16 Number of pixels: 256 Vacuum degree 4×10 -7 Pa or less Primary ion species Bi3 ++ Accelerating voltage: 30 kV Pulse width 12.5ns High mass resolution measurement Yes No charge neutralization Rear acceleration 9.5kV The battery is disassembled in an Ar atmosphere, and measurements are performed without being exposed to the atmosphere.
[0085] When coating with a plasticizer layer, it is better to mix crushed solid electrolyte into the plasticizer layer since the plasticizer is an insulator.
[0086] The material of the solid electrolyte is not particularly limited, but lithium phosphate and aluminum oxide having Li permeability are preferable.
[0087] The negative electrode active material particles preferably have a median diameter of 4.5 μm or more and 15 μm or less.
[0088] If the median diameter of the negative electrode active material particles is within this range, promotion of the reaction with the electrolyte can be prevented, and loss of electronic contacts due to expansion of the active material accompanying charge and discharge can be prevented.
[0089] [Method of manufacturing negative electrode active material] The negative electrode active material of the present invention can be produced, for example, by the following method: However, the negative electrode active material of the present invention may be produced by a method other than the method described below.
[0090] First, silicon oxide particles containing a silicon compound containing oxygen are prepared. In the following, SiO xThe case where silicon oxide represented by (0.8≦x≦1.2) is used will be described. First, a raw material that generates silicon oxide gas is heated in the presence of an inert gas and under reduced pressure at a temperature range of 900°C to 1600°C to generate silicon oxide gas. In this case, a mixture of metallic silicon powder and silicon dioxide powder can be used as the raw material. Considering the surface oxygen of the metallic silicon powder and the presence of trace oxygen in the reactor, it is desirable for the mixed molar ratio to be in the range of 0.9<metallic silicon powder / silicon dioxide powder<1.2.
[0091] The generated silicon oxide gas is solidified and deposited on the adsorption plate. Next, the temperature inside the reactor is lowered to below 100°C, and the silicon oxide deposit is taken out and pulverized into powder using a ball mill, jet mill, or the like. In this manner, silicon oxide particles can be produced. The Si crystallites in the silicon oxide particles can be controlled by changing the vaporization temperature of the raw material that generates the silicon oxide gas, or by heat treatment after the silicon compound particles are produced.
[0092] Next, a layer of a carbon material is formed on the surface of the silicon oxide particles.
[0093] The method for forming the carbon layer includes a pyrolytic CVD method. An example of the method for forming the carbon layer by the pyrolytic CVD method will be described below.
[0094] First, silicon oxide particles are placed in a furnace. Next, a hydrocarbon gas is introduced into the furnace, and the temperature inside the furnace is increased. The decomposition temperature is not particularly limited, but is preferably 950°C or less, and more preferably 850°C or less. By setting the decomposition temperature at 950°C or less, unintended disproportionation of the active material particles can be suppressed. After the temperature inside the furnace is increased to a predetermined temperature, a carbon layer is generated on the surface of the silicon compound particles. The hydrocarbon gas that is the raw material for the carbon material is not particularly limited, but is preferably C n H m In the composition, it is desirable for n to be ≦ 3. If n ≦ 3, the production cost can be reduced and the physical properties of the decomposition products can be improved.
[0095] The carbon covering the silicon oxide particles is generally formed by using the CVD method from a hydrocarbon gas as explained above, but by kneading the silicon oxide particles with an asphalt component (a hydrocarbon material derived from petroleum asphalt) and subjecting it to heat treatment at, for example, 850°C to 900°C, it is possible to obtain a carbon layer that contains nitrogen atoms (N) and is more stable and has excellent Li permeability.
[0096] Next, Li is inserted into the silicon oxide particles (silicon oxide particles coated with a carbon layer) prepared as described above. This produces negative electrode active material particles containing silicon oxide particles with lithium inserted. That is, this modifies the silicon oxide particles coated with a carbon layer, and produces a Li compound inside the silicon oxide particles. The insertion of Li is preferably performed by an oxidation-reduction method.
[0097] In the modification by the oxidation-reduction method, for example, first, lithium can be inserted by immersing silicon oxide particles coated with a carbon layer in solution A in which lithium is dissolved in an ether solvent. This solution A may further contain a polycyclic aromatic compound or a linear polyphenylene compound. After lithium insertion, active lithium can be desorbed from the silicon oxide particles coated with a carbon layer by immersing the silicon active material particles coated with a carbon layer in solution B containing a polycyclic aromatic compound or its derivative. For example, the solvent of this solution B can be an ether-based solvent, a ketone-based solvent, an ester-based solvent, an alcohol-based solvent, an amine-based solvent, or a mixed solvent thereof. Alternatively, after immersion in solution A, the silicon oxide particles coated with the obtained carbon layer may be heat-treated under an inert gas. The Li compound can be stabilized by heat treatment. After that, washing may be performed using a method such as washing with alcohol, alkaline water in which lithium carbonate is dissolved, weak acid, or pure water.
[0098] As the ether solvent used in solution A, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, dioxane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, or a mixture thereof can be used. Among these, it is particularly preferable to use tetrahydrofuran, dioxane, or 1,2-dimethoxyethane. These solvents are preferably dehydrated and deoxygenated.
[0099] Furthermore, the polycyclic aromatic compound contained in solution A may be one or more of naphthalene, anthracene, phenanthrene, naphthacene, pentacene, pyrene, picene, triphenylene, coronene, chrysene, and derivatives thereof, and the linear polyphenylene compound may be one or more of biphenyl, terphenyl, and derivatives thereof.
[0100] The polycyclic aromatic compound contained in solution B may be one or more of naphthalene, anthracene, phenanthrene, naphthacene, pentacene, pyrene, picene, triphenylene, coronene, chrysene, and derivatives thereof.
[0101] As the ether solvent for solution B, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, dioxane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and the like can be used.
[0102] As the ketone solvent, acetone, acetophenone, etc. can be used.
[0103] As the ester solvent, methyl formate, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, and the like can be used.
[0104] As the alcohol-based solvent, methanol, ethanol, propanol, isopropyl alcohol, and the like can be used.
[0105] As the amine solvent, methylamine, ethylamine, ethylenediamine, and the like can be used.
[0106] The Li silicate produced by the oxidation-reduction method is Li4SiO4, but by heat treatment it can be converted to other Li silicates such as Li2SiO3. The degree of crystallization of Li silicate and Si changes depending on the temperature at this time. In addition, the reaction temperature during Li insertion also affects the degree of crystallization of Li silicate and Si.
[0107] The state of the Li silicate can be controlled by filtering the material that has been doped with Li using the oxidation-reduction method and then subjecting it to heat treatment at 400°C to 650°C.
[0108] At this time, it is important to perform the heat treatment in a vacuum state or under an inert gas.
[0109] The heat treatment device is not limited to a specific device, but it is preferable to use a uniform heat treatment device such as a rotary kiln.
[0110] At this time, various Li silicate states can be created by using factors such as the vacuum state, inert gas flow rate (internal pressure), retort thickness, and rotation speed.
[0111] Similarly, the growth of silicon or the amorphization of silicon can be controlled.
[0112] Next, at least a portion of the outermost layer of the Li-doped silicon oxide particles is coated with a layer of a plasticizer.
[0113] The coating method here is not particularly limited, but can be performed, for example, by the following method.
[0114] The plasticizer is dissolved in a solvent such as diethyl ether that can be used as the solvent for solution A to obtain a plasticizer solution. Next, the particles obtained by the Li-doping process are mixed with the solution in which the plasticizer is dissolved, and then the solvent is volatilized using a spray dryer to form a layer of the plasticizer on the surface of the particles. After that, the solvent is completely removed by vacuum drying. This results in the negative electrode active material of the present invention.
[0115] [Negative electrode] The negative electrode of the present invention comprises the negative electrode active material of the present invention.
[0116] Next, the configuration of the negative electrode of the present invention will be described with reference to an example. FIG. 1 shows a schematic cross-sectional view of one example of the negative electrode of the present invention. As shown in FIG. 1, the negative electrode 10 has a configuration having a negative electrode active material layer 12 on a negative electrode current collector 11. This negative electrode active material layer 12 may be provided on both sides of the negative electrode current collector 11 as shown in FIG. 1, or may be provided on only one side. Furthermore, the negative electrode of the present invention does not necessarily require the negative electrode current collector 11.
[0117] Each component will be described below.
[0118] [Negative electrode current collector] The negative electrode current collector 11 is made of a material having excellent electrical conductivity and excellent mechanical strength. Examples of the conductive material that can be used for the negative electrode current collector 11 include copper (Cu) and nickel (Ni). It is preferable that this conductive material is a material that does not form an intermetallic compound with lithium (Li).
[0119] The negative electrode current collector 11 preferably contains carbon (C) and / or sulfur (S) in addition to the main elements. This is because the physical strength of the negative electrode current collector 11 is improved. In particular, when the current collector has an active material layer that expands during charging, if the current collector contains the above elements, this has the effect of suppressing deformation of the electrode including the current collector. The contents of the above contained elements are not particularly limited, but are preferably 100 mass ppm or less for each. This is because a higher deformation suppression effect can be obtained.
[0120] The surface of the negative electrode current collector 11 may be roughened or may not be roughened. The roughened negative electrode current collector is, for example, a metal foil that has been electrolytically treated, embossed, or chemically etched. The unroughened negative electrode current collector is, for example, a rolled metal foil.
[0121] [Negative electrode active material layer] The negative electrode active material layer 12 contains the negative electrode active material of the present invention capable of absorbing and releasing lithium ions, and may further contain other materials such as a negative electrode binder and a conductive assistant from the viewpoint of battery design. The negative electrode active material contains negative electrode active material particles, and the negative electrode active material particles contain silicon oxide particles coated with a carbon layer.
[0122] The negative electrode active material layer 12 may also contain a mixed negative electrode active material containing the negative electrode active material of the present invention (silicon-based negative electrode active material) and a carbon-based active material. This reduces the electrical resistance of the negative electrode active material layer and can alleviate the expansion stress caused by charging. Examples of the carbon-based active material that can be used include pyrolytic carbons, cokes, glassy carbon fibers, organic polymer compound sintered bodies, and carbon blacks.
[0123] The negative electrode binder contained in the negative electrode active material layer 12 may be, for example, one or more of polymer materials, synthetic rubber, etc. Examples of the polymer materials include polyvinylidene fluoride, polyimide, polyamideimide, aramid, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, carboxymethyl cellulose, etc. Examples of the synthetic rubber include styrene butadiene rubber, fluorine-based rubber, ethylene propylene diene, etc.
[0124] As the negative electrode conductive assistant, for example, one or more of carbon materials such as carbon black, acetylene black, graphite, Ketjen black, carbon nanotubes, and carbon nanofibers can be used.
[0125] The negative electrode active material layer 12 is formed, for example, by a coating method, in which the silicon-based negative electrode active material is mixed with the binder and, if necessary, a conductive additive and a carbon-based active material, and then the mixture is dispersed in an organic solvent, water, or the like and coated.
[0126] Specifically, for example, the process is as follows. First, the negative electrode active material of the present invention prepared as described above is mixed with other materials such as a negative electrode binder and a conductive assistant to form a negative electrode mixture, and then an organic solvent or water is added to form a slurry. Next, the above-mentioned slurry is applied to the surface of the negative electrode current collector and dried to form a negative electrode active material layer. At this time, hot pressing or the like may be performed as necessary. In this manner, the negative electrode of the present invention can be prepared.
[0127] The negative electrode active material of the present invention is particularly suitable for forming a slurry using water, but can also be applied to forming a slurry using an organic solvent.
[0128] <Lithium-ion secondary battery> The negative electrode of the present invention can be used in the negative electrode of a non-aqueous electrolyte secondary battery, for example, a lithium ion secondary battery.
[0129] Next, as a specific example of a nonaqueous electrolyte secondary battery in which the negative electrode of the present invention can be used, an example of a laminate film type lithium ion secondary battery will be described.
[0130] [Configuration of laminated film type secondary battery] The laminate film type lithium ion secondary battery 30 shown in FIG. 2 is a battery in which a wound electrode body 31 is housed inside a sheet-like exterior member 35. This wound electrode body 31 has a separator between the positive electrode and the negative electrode and is wound. There are also cases where the electrode body is not wound, but a laminate having a separator between the positive electrode and the negative electrode is housed. In either electrode body, a positive electrode lead 32 is attached to the positive electrode, and a negative electrode lead 33 is attached to the negative electrode. The outermost periphery of the electrode body 31 is protected by a protective tape.
[0131] The positive electrode lead 32 and the negative electrode lead 33 are led out in one direction, for example, from the inside to the outside of the exterior member 35. The positive electrode lead 32 is formed of a conductive material such as aluminum, and the negative electrode lead 33 is formed of a conductive material such as nickel or copper.
[0132] The exterior member 35 is, for example, a laminate film in which a fusion layer, a metal layer, and a surface protection layer are laminated in this order, and the outer peripheral edges of the fusion layers of the two films of this laminate film are fused together or pasted together with an adhesive so that the fusion layer faces the electrode body 31. The fusion part is, for example, a film such as polyethylene or polypropylene, and the metal part is aluminum foil, etc. The protection layer is, for example, nylon, etc.
[0133] To prevent outside air from entering, an adhesive film 34 is inserted between the exterior member 35 and each of the positive electrode lead 32 and the negative electrode lead 33. The material for this is, for example, polyethylene, polypropylene, or polyolefin resin.
[0134] Each component will be described below.
[0135] [Positive electrode] The positive electrode has a positive electrode active material layer on either or both sides of a positive electrode current collector, similar to the negative electrode 10 in FIG.
[0136] The positive electrode current collector is made of a conductive material such as aluminum.
[0137] The positive electrode active material layer contains one or more types of positive electrode materials (positive electrode active materials) capable of absorbing and releasing lithium ions, and may contain other materials such as a positive electrode binder, a positive electrode conductive assistant, and a dispersant depending on the design.
[0138] As the positive electrode material, a lithium-containing compound is desirable. Examples of this lithium-containing compound include a composite oxide composed of lithium and a transition metal element, or a phosphate compound having lithium and a transition metal element. Among these positive electrode materials, a compound having at least one of nickel, iron, manganese, and cobalt is preferable. As these chemical formulas, for example, Li x M1O2 or Li y M2PO4. In the formula, M1 and M2 represent at least one transition metal element. The values of x and y represent different values depending on the charge and discharge state of the battery, but generally are represented by 0.05 ≦ x ≦ 1.10 and 0.05 ≦ y ≦ 1.10.
[0139] Examples of the composite oxide having lithium and a transition metal element include lithium cobalt composite oxide (Li x CoO2), lithium nickel composite oxide (Li x NiO2), and lithium nickel cobalt composite oxide. Examples of the lithium nickel cobalt composite oxide include lithium nickel cobalt aluminum composite oxide (NCA) and lithium nickel cobalt manganese composite oxide (NCM).
[0140] Examples of the phosphate compound having lithium and a transition metal element include lithium iron phosphate compound (LiFePO4) or lithium iron manganese phosphate compound (LiFe 1-u Mn u PO4 (0 < u < 1)). By using these positive electrode materials, a high battery capacity can be obtained, and excellent cycle characteristics can also be obtained.
[0141] As the positive electrode binder, for example, any one or more of a polymer material, a synthetic rubber, etc. can be used. Examples of the polymer material include polyvinylidene fluoride, polyimide, polyamideimide, aramid, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, carboxymethyl cellulose, etc. Examples of the synthetic rubber include styrene-butadiene rubber, fluorine rubber, ethylene propylene diene, etc.
[0142] As the positive electrode conductive assistant, for example, one or more of carbon materials such as carbon black, acetylene black, graphite, Ketjen black, carbon nanotubes, and carbon nanofibers can be used.
[0143] [Negative electrode] The negative electrode of the present invention is used as the negative electrode of the secondary battery. It is preferable that the negative electrode constituting this secondary battery has a negative electrode charge capacity larger than the electric capacity (charge capacity as a battery) obtained from the positive electrode active material. This makes it possible to suppress the deposition of lithium metal on the negative electrode.
[0144] In this example, the positive electrode active material layer is provided on a part of both sides of the positive electrode current collector, and similarly, the negative electrode active material layer of the present invention is provided on a part of both sides of the negative electrode current collector. In this case, for example, it is preferable that the negative electrode active material layer provided on the negative electrode current collector has a region where the opposing positive electrode active material layer does not exist. This is for the purpose of designing a stable battery.
[0145] The region where the negative electrode active material layer and the positive electrode active material layer do not face each other is hardly affected by charging and discharging, so the state of the negative electrode active material layer is maintained as it is immediately after formation, and the composition of the negative electrode active material can be accurately examined with good reproducibility regardless of the presence or absence of charging and discharging.
[0146] [Separator] The separator separates the lithium metal or the positive electrode from the negative electrode, and allows lithium ions to pass through while preventing current short circuit caused by contact between the two electrodes. The separator is formed of a porous film made of, for example, synthetic resin or ceramic, and may have a laminated structure in which two or more types of porous films are laminated. Examples of synthetic resins include polytetrafluoroethylene, polypropylene, and polyethylene.
[0147] [Electrolyte] At least a portion of each of the positive electrode active material layer and the negative electrode active material layer, or the separator, is impregnated with a liquid nonaqueous electrolyte (electrolytic solution). This electrolytic solution contains an electrolyte salt dissolved in a solvent, and may contain other materials such as additives.
[0148] The solvent may be, for example, a non-aqueous solvent. Examples of non-aqueous solvents include ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, 1,2-dimethoxyethane, and tetrahydrofuran. Among these, it is desirable to use at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. This is because better characteristics can be obtained. In this case, more advantageous characteristics can be obtained by combining a high-viscosity solvent such as ethylene carbonate or propylene carbonate with a low-viscosity solvent such as dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. This is because the dissociation and ion mobility of the electrolyte salt are improved.
[0149] When an alloy-based negative electrode is used, it is particularly desirable that the solvent contains at least one of halogenated chain carbonates or halogenated cyclic carbonates. This allows a stable coating to be formed on the surface of the negative electrode active material during charging and discharging, particularly during charging. Here, the halogenated chain carbonate is a chain carbonate having a halogen as a constituent element (at least one hydrogen is substituted with a halogen). Also, the halogenated cyclic carbonate is a cyclic carbonate having a halogen as a constituent element (i.e., at least one hydrogen is substituted with a halogen).
[0150] The type of halogen is not particularly limited, but fluorine is preferred because it forms a better coating than other halogens. Also, the more halogens there are, the more desirable they are because the resulting coating is more stable and the decomposition reaction of the electrolyte is reduced.
[0151] Examples of halogenated chain carbonates include fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, etc. Examples of halogenated cyclic carbonates include 4-fluoro-1,3-dioxolan-2-one, 4,5-difluoro-1,3-dioxolan-2-one, etc.
[0152] It is preferable that the solvent additive contains an unsaturated carbon-bonded cyclic carbonate. This is because a stable coating is formed on the negative electrode surface during charging and discharging, and the decomposition reaction of the electrolyte can be suppressed. Examples of the unsaturated carbon-bonded cyclic carbonate include vinylene carbonate and vinylethylene carbonate.
[0153] It is also preferable that the solvent additive contains sultone (cyclic sulfonic acid ester), because this improves the chemical stability of the battery. Examples of sultones include propane sultone and propene sultone.
[0154] Furthermore, it is preferable that the solvent contains an acid anhydride, because this improves the chemical stability of the electrolyte. As the acid anhydride, for example, propane disulfonic acid anhydride can be mentioned.
[0155] The electrolyte salt may include at least one of light metal salts such as lithium salts, for example. Examples of the lithium salt include lithium hexafluorophosphate (LiPF6) and lithium tetrafluoroborate (LiBF4).
[0156] The content of the electrolyte salt is preferably 0.5 mol / kg or more and 2.5 mol / kg or less relative to the solvent, because high ionic conductivity can be obtained.
[0157] [Manufacturing method of laminate film type secondary battery] The laminate film type secondary battery described above can be manufactured, for example, by the following procedure.
[0158] First, a positive electrode is prepared using the above-mentioned positive electrode material. First, a positive electrode active material is mixed with a positive electrode binder, a positive electrode conductive assistant, etc., if necessary, to prepare a positive electrode mixture, which is then dispersed in an organic solvent to prepare a positive electrode mixture slurry. Next, the mixture slurry is applied to a positive electrode current collector using a coating device such as a knife roll or a die coater having a die head, and the mixture is dried with hot air to obtain a positive electrode active material layer. Finally, the positive electrode active material layer is compression molded using a roll press machine or the like. At this time, heating may be performed, and compression may be repeated multiple times.
[0159] Next, following the same procedure as in the production of the negative electrode 10 described above, a negative electrode active material layer is formed on the negative electrode current collector to produce the negative electrode.
[0160] When preparing the positive and negative electrodes, active material layers are formed on both sides of the positive and negative current collectors, respectively. At this time, the lengths of the active material applied on both sides of each electrode may be offset (see FIG. 1).
[0161] Next, the electrolyte is adjusted. Next, the positive electrode lead 32 is attached to the positive electrode current collector by ultrasonic welding or the like, and the negative electrode lead 33 is attached to the negative electrode current collector. Next, the positive electrode and the negative electrode are laminated with a separator interposed therebetween, and then wound to prepare the wound electrode body 31, and a protective tape is attached to the outermost periphery. Next, the wound electrode body 31 is molded to have a flat shape. Next, the wound electrode body 31 is sandwiched between folded film-like exterior members 35, and then the insulating parts of the exterior members are bonded to each other by a heat fusion method, and the wound electrode body 31 is sealed in a state in which only one direction is open. Next, an adhesive film 34 is inserted between the positive electrode lead 32 and the negative electrode lead 33 and the exterior member 35. Next, a predetermined amount of the above-prepared electrolyte is poured from the open part, and vacuum impregnation is performed. After the impregnation, the open part is bonded by a vacuum heat fusion method. In this manner, the laminate film type secondary battery 30 can be manufactured.
[0162] In the non-aqueous electrolyte secondary battery such as the laminate film type secondary battery 30 produced above, the negative electrode utilization rate during charging and discharging is preferably 93% or more and 99% or less. If the negative electrode utilization rate is in the range of 93% or more, the initial charge efficiency does not decrease and the battery capacity can be greatly improved. In addition, if the negative electrode utilization rate is in the range of 99% or less, Li does not precipitate and safety can be ensured. EXAMPLES
[0163] The present invention will be specifically described below using examples and comparative examples, but the present invention is not limited to these.
[0164] (Examples 1 to 3) First, the negative electrode active material was prepared as follows. A raw material obtained by mixing metal silicon and silicon dioxide was introduced into a reactor. In this reactor, the raw material was vaporized in a vacuum atmosphere of 10 Pa and deposited on an adsorption plate. After sufficient cooling, the deposit was taken out and pulverized in a ball mill. The SiO of the silicon oxide particles thus obtained was x The value of x was 1.0.
[0165] Next, the particle size of the silicon oxide particles was adjusted by classification.Then, the surface of the silicon oxide particles was coated with a carbon material by thermal decomposition CVD at a temperature range of 700 to 950°C.
[0166] Next, lithium was inserted into silicon oxide particles by an oxidation-reduction method using an ether-based solvent with a water content reduced to 50 ppm.
[0167] In Examples 1 and 3, the material was then further modified by heating in the range of 450° C. to 700° C. As a result, the state of the Li silicate was controlled to the state shown in Table 1 below.
[0168] After the modification, the outermost surface of the silicon oxide particles was coated with a layer of dioctyl phthalate, a plasticizer, using the spray drying method described above. The thickness of the plasticizer layer was 1 nm.
[0169] In this manner, the negative electrode active materials of the respective Examples containing the negative electrode active material particles were obtained.
[0170] The median diameter of the negative electrode active material particles contained in each negative electrode active material, and the ratio of the peak intensity A due to the Si(111) crystal plane to the peak intensity B due to the Li2SiO3(111) crystal plane are shown in Table 1 below. The intensity ratio A / B was confirmed by XRD. Also, it was confirmed by XRD that the Si contained in each negative electrode active material was amorphous.
[0171] Next, the negative electrode active material (active material containing modified silicon oxide particles) prepared as described above, graphite, conductive additive 1 (carbon nanotubes, CNT), conductive additive 2 (carbon particles having a median diameter of approximately 50 nm), sodium polyacrylate, and carboxymethyl cellulose (hereinafter referred to as CMC) were mixed in a dry mass ratio of 9.3:83.7:1:1:4:1, and then diluted with pure water to form a negative electrode mixture slurry.
[0172] At this time, the stability of the slurry was monitored by its pot life, and it was confirmed whether it was stable after 72 hours. This can be judged by whether hydrogen gas is released from the slurry.
[0173] In addition, an electrolytic copper foil having a thickness of 15 μm was used as the negative electrode current collector. This electrolytic copper foil contained carbon and sulfur at a concentration of 70 mass ppm each. Finally, the negative electrode mixture slurry was applied to the negative electrode current collector and dried at 100° C. for 1 hour in a vacuum atmosphere. After drying, the deposition amount of the negative electrode active material layer per unit area on one side of the negative electrode (also called the area density) was 7.0 mg / cm 2 It was.
[0174] [Assembling a coin battery for testing] Next, the solvents ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed, and then the electrolyte salt (lithium hexafluorophosphate: LiPF6) was dissolved to prepare an electrolyte solution. In this case, the solvent composition was EC:DMC=30:70 in volume ratio, and the content of the electrolyte salt was 1 mol / kg relative to the solvent. As additives, vinylene carbonate (VC) and fluoroethylene carbonate (FEC) were added in amounts of 1.0 mass% and 2.0 mass%, respectively.
[0175] Next, a coin battery was assembled as follows: First, a 1 mm thick Li foil was punched out to a diameter of 16 mm and attached to an aluminum clad.
[0176] Next, the negative electrode obtained above was punched out to a diameter of 15 mm, and this was placed opposite a Li foil attached to an aluminum clad via a separator. After injection of an electrolyte, a 2032 coin battery was produced. [Measurement of initial efficiency] The initial efficiency was measured under the following conditions. First, the coin battery for the initial efficiency test was charged (initial charge) in CCCV mode with a charge rate equivalent to 0.03C. CV was 0V and the end current was 0.04mA. Next, CC discharge (initial discharge) was performed with a discharge rate of 0.03C and an end voltage of discharge of 1.2V.
[0177] When investigating the initial charge / discharge characteristics, the initial efficiency (hereinafter sometimes referred to as initial efficiency) was calculated using the formula: initial efficiency (%) = (initial discharge capacity / initial charge capacity) x 100.
[0178] [Production and evaluation of lithium-ion secondary batteries] From the initial data obtained, the counter positive electrode was designed so that the utilization rate of the negative electrode would be 95%. The utilization rate was calculated from the capacity of the positive and negative electrodes obtained with the counter electrode Li according to the following formula. Utilization rate = (positive electrode capacity - negative electrode loss) / (negative electrode capacity - negative electrode loss) x 100 Based on this design, lithium ion secondary batteries of the examples and comparative examples were manufactured. Battery evaluation was performed on each of the lithium ion secondary batteries of the examples and comparative examples.
[0179] The cycle characteristics were investigated as follows. First, in order to stabilize the battery, two cycles of charge and discharge were performed at 0.2C in an atmosphere of 25°C, and the discharge capacity of the second cycle was measured. The battery cycle characteristics were calculated from the discharge capacity of the third cycle, and the battery test was stopped after 100 cycles. Charge and discharge were performed at 0.7C and 0.5C. The charge voltage was 4.3V, the discharge end voltage was 2.5V, and the charge end rate was 0.07C.
[0180] (Comparative Examples 1 to 6) In Comparative Examples 1, 3, and 5, the negative electrode active materials of each Comparative Example were produced in the same manner as in Example 2, except that the outermost layer of the silicon oxide particles was not covered with a plasticizer layer. In Comparative Examples 3 and 5, a modification treatment was carried out after Li doping, and the state of Li silicate was controlled as shown in Table 1 below.
[0181] In Comparative Examples 1, 3, and 5, the negative electrode mixture slurry was prepared in the same manner as above using the negative electrode active material of each Comparative Example. In addition, on the same day as the negative electrode mixture slurry was prepared, the negative electrode was prepared in the same manner as above using the prepared negative electrode mixture slurry.
[0182] In Comparative Examples 2, 4, and 6, the same negative electrode composite slurries as those in Comparative Examples 1, 3, and 5, respectively, were prepared, and on the following day, negative electrodes were prepared using the prepared negative electrode composite slurries in the same manner as above.
[0183] (Examples 4 to 18) In Examples 4 to 18, negative electrode active materials and negative electrodes were prepared in the same manner as in Example 1, except that the plasticizer used was changed to one shown in Table 1. In Example 15, N-ethyl- o In Example 15, a mixture of N-toluenesulfonamide and N-ethyl-p-toluenesulfonamide was used, and in Example 16, a mixture of o-toluenesulfonamide and p-toluenesulfonamide was used.
[0184] (Examples 19 to 24) A negative electrode active material and a negative electrode were produced in the same manner as in Example 8, except that the thickness of the plasticizer layer was changed to that shown in Table 2.
[0185] (Example 25) In Example 25, a negative electrode active material and a negative electrode were produced in the same manner as in Example 8, except that the carbon layer was formed using petroleum asphalt.
[0186] Specifically, petroleum asphalt was dissolved in toluene, separated by spray drying, and then heat-treated. This resulted in a hydrocarbon material derived from petroleum asphalt. The silicon oxide particles prepared by the procedure described above were then classified to adjust the particle size, and then kneaded with the hydrocarbon material derived from petroleum asphalt and heat-treated at 870°C. Thereafter, modification and coating with a layer of plasticizer were performed in the same manner as in Example 8 to obtain the negative electrode active material of Example 25.
[0187] (Examples 26 and 27) In Examples 26 and 27, negative electrode active materials and negative electrodes were prepared in the same manner as in Example 8, except that when the plasticizer layer was formed, sufficiently crushed lithium phosphate, or lithium phosphate and aluminum oxide, was mixed into the plasticizer solution so as to be dispersed in the film.
[0188] (Examples 28 and 29) In Example 28, a negative electrode active material and a negative electrode were produced in the same manner as in Example 26, except that the carbon layer was formed in the same manner as in Example 25.
[0189] In Example 29, a negative electrode active material and a negative electrode were produced in the same manner as in Example 27, except that the carbon layer was formed in the same manner as in Example 25.
[0190] (Examples 30 to 34) In Examples 30 to 34, negative electrode active materials and negative electrodes were produced in the same manner as in Example 8, except that the crystallinity of Si and Li silicate was changed as shown in Table 2 below.
[0191] Specifically, in Examples 30 to 34, an ether solvent was used, and Li was inserted at a temperature 10° C. or more lower than the boiling point of the solvent. In addition, the temperature of the subsequent heat treatment was changed in the range of 450° C. or more and 650° C. or less to control the crystallinity of the Li silicate and the crystallinity of Si.
[0192] (Examples 35 to 41) In Examples 35 to 41, negative electrode active materials were produced in the same manner as in Example 8, except that the particle size of the silicon oxide particles was adjusted by classification so that the median diameter of the negative electrode active material particles produced would be the value shown in Table 2 below.
[0193] The parameters of the negative electrode active materials of the Examples and Comparative Examples are summarized in Tables 1 and 2. In addition, the capacity retention rates up to 500 cycles of the lithium ion secondary batteries of the Examples and Comparative Examples and the stability of the negative electrode composite slurries prepared using each negative electrode active material are summarized in Tables 3 and 4.
[0194] [Table 1]
[0195] [Table 2]
[0196] [Table 3]
[0197] [Table 4]
[0198] [evaluation] Comparative Examples 1 to 6 are cases where no plasticizer was used in the outermost layer to form a slurry. For each Li silicate, good properties were obtained on the day of coating (slurrying), as shown in Table 3 for Comparative Examples 1, 3, and 5. However, the next day, gas was generated from the slurry and the viscosity of the thickener decreased, resulting in a significant deterioration in long-term battery properties, as shown in Table 3 for Comparative Examples 2, 4, and 6.
[0199] Moreover, the pot life of the slurry prepared using the negative electrode active materials of the comparative examples was 18 hours or less, as shown in Table 3. Since the pot life of a slurry is generally required to be 48 hours or more, this result means that the negative electrode active materials of Comparative Examples 1 to 6 are not industrially useful.
[0200] On the other hand, as shown in Tables 3 and 4, the negative electrode active materials of Examples 1 to 41 exhibited excellent long-term battery characteristics even when the negative electrode was prepared by coating the slurry on the day after its preparation.
[0201] Moreover, the pot life of the slurries prepared using the negative electrode active materials of Examples 1 to 41 was 48 hours or more, as shown in Tables 3 and 4. This result means that the negative electrode active materials of Examples 1 to 41 meet the pot life requirements of general slurries and are therefore industrially useful.
[0202] Each embodiment will be described below.
[0203] In Example 1, after doping with Li, a heat load was applied to form Li2SiO3, and a layer of dioctyl phthalate was formed as a plasticizer layer on the outermost surface of the negative electrode active material particles. In this example, a good quality coating film was obtained by the plasticizer, and it is believed that high slurry stability was achieved.
[0204] In Example 2, after doping with Li, a layer of dioctyl phthalate was formed as a plasticizer layer on the outermost surface of the negative electrode active material particles. In this example, although Li4SiO4 present inside the bulk is an unstable substance, the minimum required durability (slurry stability) of 48 hours was confirmed.
[0205] In Example 3, after Li doping, a plasticizer layer was formed on the outermost surface of the negative electrode active material particles while leaving some Li6Si2O7 inside the bulk. The slurry prepared using the negative electrode active material of Example 3 was slightly unstable compared to Example 1, but its durability (slurry stability) for 72 hours was confirmed.
[0206] Stability was confirmed using various plasticizers in Examples 4 to 18. As a result, it was found that good slurry stability was obtained even when the type of plasticizer was changed.
[0207] The thickness of the plasticizer layer was changed in Examples 19 to 24. It was confirmed that sufficient durability (slurry stability) was obtained even when the thickness of the plasticizer layer was 0.1 nm.
[0208] In the examples and comparative examples, the film thickness was calculated from the change in mass before and after treatment (it was too thin to observe directly), but it is believed that the film is not completely covered and that some parts are exposed. However, it was confirmed that the film thickness is within the range that can withstand practical use.
[0209] From the results of Examples 8 and 19 to 24, it can be seen that better cycle characteristics were exhibited when the thickness of the plasticizer layer was 0.1 to 10 nm inclusive. This is believed to be because the plasticizer layer can exhibit sufficient Li permeability if its thickness is within the range of 0.1 to 10 nm inclusive.
[0210] From a comparison of the results of Example 25 and Example 8, it was confirmed that even if the carbon layer was formed using petroleum asphalt, properties similar to those of CVD could be obtained.
[0211] Examples 26 to 29 are examples in which pulverized solid electrolyte is mixed into the plasticizer layer. Comparing the results of Examples 8 and 25 with those of Examples 26 to 29, it can be seen that the cycle characteristics can be further improved by mixing pulverized solid electrolyte into the plasticizer layer. From these results, it was confirmed that by mixing pulverized solid electrolyte into the plasticizer layer, Li ions passing through the plasticizer layer can smoothly enter and exit, improving the battery characteristics.
[0212] Fig. 3 shows an X-ray photoelectron spectroscopy spectrum of the surface of the negative electrode active material of Example 1. Also, Fig. 4 shows a TOF-SIMS spectrum of the surface of the negative electrode active material of Example 1. Table 5 below shows the TOF-SIMS measurement conditions.
[0213] [Table 5]
[0214] From the X-ray photoelectron spectroscopy spectrum shown in FIG. 3, dioctyl phthalate on the outermost surface of the negative electrode active material of Example 1 could not be confirmed. On the other hand, from the TOF-SIMS spectrum shown in FIG. 24 H 38 O4Li + The presence of this peak revealed that a layer of dioctyl phthalate was present on the outermost surface of the negative electrode active material particles.
[0215] From the results of Examples 30 to 34 and Example 8, it was found that the crystallinity of Si is preferably substantially amorphous.
[0216] This Li silicate and the crystallization of Si estimated from XRD are important control parameters, and vary greatly depending on the conditions during Li insertion and heat treatment conditions.
[0217] Furthermore, from the results shown in Tables 3 and 4, it is apparent that although Examples 35 to 41 and Example 8 have different median diameters of the negative electrode active material particles, they were able to similarly exhibit excellent cycle battery characteristics.
[0218] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]
[0219] REFERENCE SIGNS LIST 10... negative electrode, 11... negative electrode current collector, 12... negative electrode active material layer, 30... lithium ion secondary battery (laminate film type), 31... electrode body, 32... positive electrode lead, 33... negative electrode lead, 34... adhesive film, 35... exterior member.
Claims
1. A negative electrode active material including negative electrode active material particles, The negative electrode active material particles contain silicon oxide particles coated with a carbon layer, The silicon oxide particles are at least partially composed of Li 2 SiO 3 , Li 4 SiO 4 and Li 6 S 2 O 7 At least one selected from the group consisting of At least a part of the outermost layer of the negative electrode active material particles is covered with a layer of a plasticizer.
2. 2. The negative electrode active material according to claim 1, wherein the thickness of the plasticizer layer is 0.1 nm or more and 10 nm or less.
3. 3. The negative electrode active material according to claim 1, wherein the carbon layer contains nitrogen atoms in a part thereof.
4. 4. The negative electrode active material according to claim 3, wherein the carbon layer is formed using a hydrocarbon material derived from petroleum asphalt as a starting material, and contains the nitrogen atoms in a portion thereof.
5. The negative electrode active material according to any one of claims 1 to 4, characterized in that the plasticizer includes at least one selected from the group consisting of a phthalate ester plasticizer, an adipic acid ester plasticizer, a phosphate ester plasticizer, and a sulfonamide plasticizer.
6. The negative electrode active material according to claim 5, characterized in that the plasticizer includes at least one selected from the group consisting of dioctyl phthalate, dibutoxyethyl phthalate, diisononyl phthalate, diisodecyl phthalate, diundecyl phthalate, bis(2-ethylhexyl) adipate, diisononyl adipate, diisodecyl adipate, bis(2-butoxyethyl) adipate, triphenyl phosphate, phthalic acid-based polyester, adipic acid-based polyester, epoxidized vegetable oil, p-toluenesulfonamide, N-ethyl-o-toluenesulfonamide, N-ethyl-p-toluenesulfonamide, o-toluenesulfonamide, N-n-butylbenzenesulfonamide, and N-cyclohexyl-p-toluenesulfonamide.
7. 7. The negative electrode active material according to claim 1, wherein the plasticizer layer further contains a solid electrolyte.
8. 8. The negative electrode active material according to claim 7, wherein the solid electrolyte contains lithium phosphate and / or aluminum oxide.
9. The negative electrode active material particles have a peak due to a Si (111) crystal plane obtained by X-ray diffraction using Cu-Kα radiation before charging and discharging the negative electrode active material particles, and the crystallite size corresponding to the crystal plane is 5.0 nm or less, and Li 2 SiO 3 The ratio A / B of the intensity A of the peak due to the Si (111) crystal plane to the intensity B of the peak due to the (111) crystal plane is expressed by the following formula (1): 0.4≦A / B≦1.0 (1) 8. The negative electrode active material according to claim 1, which satisfies the following:
10. 10. The negative electrode active material according to claim 1, wherein the negative electrode active material particles have a median diameter of 4.5 μm or more and 15 μm or less.
11. A negative electrode comprising the negative electrode active material according to any one of claims 1 to 10.
Citation Information
Patent Citations
Silicon-oxygen composite negative electrode material, preparation method thereof and lithium ion battery
CN111710845A
Nonaqueous electrolytic secondary battery and its manufacture
JP1994325765A
Lithium secondary battery
JP2001185127A
Non-aqueous electrolyte secondary battery
JP2002042806A
Battery
JP2006114454A
